KAJIAN SIFAT FISIKA TANAH PADA BERBAGAI PENGGUNAAN LAHAN DI DAERAH GUNUNG TANDIKEK, KABUPATEN PADANG PARIAMAN - Burhanuddin Burhanuddin; Yulinar Zubaidah; Amrizal Saidi; Del Yunita (Jurnal Solum, 2010)
The research was conducted in Tandikek mountain region, Padang Pariaman District, then at soil laboratory, Faculty of Agriculture, Andalas University as well as at physical and soil mineralogy laboratory, Faculty of Agriculture, Jambi University from October 2002 to February 2003. The research was designed in the form of field survey. Determination of the location was based on the land uses. There were 5 land use types, those were mixture farm, paddy soil, secondary forest, cinnamon, and coconut. The results showed that physical nature of soil under mixture farm, paddy soil, secondary forest, cinnamon, and coconut varied at texture (dusty plates), organic contents (high-very high), slowly drainage pore (PDL) and pore of water available (PAT) which were not significantly different among the five land uses. Permeability of total pore space (TRP) and fast drainage pore (PDC) were high at land use of cinnamon and not significantly different at land uses of paddy soil, secondary forest, and coconut. Key word : soil physical characteristics, land uses.